Gambaran Tingkat Pengetahuan dan Perilaku Masyarakat dalam Upaya Pencegahan Penularan COVID 19 di Wilayah Kerja Puskesmas III Denpasar Utara - Ni Putu Mia Devihapsari; I Dewa Agung Sudarsana; I Made Sudarma Adiputra (Universitas Baiturrahim, 2021)
COVID 19 is a new type of disease caused by SARS-CoV2 which attacks the respiratory system with a fast and aggressive spread. Human-to-human spread is the main source of transmission for COVID 19. Public knowledge about COVID 19 is important during this pandemic and affects the incidence and prevention behavior of COVID 19. This study aims to determine the level of knowledge and behavior of the community in efforts to prevent transmission. COVID 19. This research uses a quantitative descriptive design. The number of samples who participated in this study were 241 respondents, using simple random sampling technique. This research was conducted in Peguyangan Village from 01st to 24th December 2020. The research instrument used was an google form regarding knowledge and behavior. The results showed that respondents had good knowledge of COVID 19 (51.0%), quite a lot (29.0%) and less (19.1%). Meanwhile, respondents who had good behavior to prevent COVID 19 were (88.0%), sufficient behavior was (12.0%) of respondents and had less behavior (0%). Based on the results of the study, it can be concluded that respondents have good knowledge about COVID 19 and good behavior to prevent the transmission of COVID 19. The community is expected to work together and remain obedient in implementing COVID 19 prevention behavior to reduce the spread in the community